Effects of Unilateral Intermediate Cervical Plexus Block on the Diaphragmatic Function in Patients Undergoing Unilateral Thyroidectomy: A Randomized Controlled Study - Han C; Shao P; Li H; Shi R; Wang Y (Journal of Pain Research, 2022)
Chao Han,1,2 Peiqi Shao,1 Huili Li,1 Rong Shi,1 Yun Wang1 1Department of Anesthesiology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Anesthesiology, Beijing Longfu Hospital, Beijing, People’s Republic of ChinaCorrespondence: Yun Wang, Department of Anesthesiology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of China, Email wangyun129@ccmu.edu.cnBackground and Purpose: Although unilateral intermediate cervical plexus block (ICPB) can be used for perioperative analgesia in neck surgery, its effect on diaphragm function remains controversial. This prospective study aimed to examine whether unilateral ICPB with different concentrations of ropivacaine resulted in the diaphragmatic dysfunction in unilateral thyroidectomy.Methods: A total of 54 patients scheduled to undergo unilateral thyroidectomy under general anesthesia were randomly allocated to receive either 10 mL of 0.3% (Group L) or 0.5% (Group H) ropivacaine for ICPB. General anesthesia was then administered for surgery. The diaphragm thickness and diaphragmatic excursion were measured at three different times: before the ICPB, at 40 min and 4 h after the block. The primary outcome was the incidence of diaphragmatic dysfunction of the block side at 40 min and 4 h after ICPB. Secondary outcomes included the maximum pain score within 24 h after the surgery, rescue analgesics within 24 h after the surgery, and time to first ambulation.Results: The incidence of diaphragmatic dysfunction on the block side of Group H was higher than that of Group L at 40 min after block (58% vs 29%, P = 0.01). However, the incidence of diaphragmatic dysfunction was comparable between Group H and Group L (65% vs 46%) at 4 h after block placement. Within 24 h after the operation, the maximum VAS pain score of Group H was significantly lower than Group L (P = 0.04), and fewer patients in Group H required rescue analgesics (P < 0.01).Conclusion: The ICPB with different concentrations of ropivacaine can induce the ipsilateral diaphragmatic dysfunction. The high concentration of ropivacaine results in higher incidence of diaphragmatic dysfunction at 40 min, but comparable incidence at 4 h after block compared with lower concentration of ropivacaine.Chinese Clinical Trial Registry: ChiCTR2000029348.Keywords: intermediate cervical plexus block, regional block, diaphragmatic dysfunction, ultrasound